Berat Bagian-Bagian Karkas Ayam Ras Pedaging Umur 5 Minggu Yang Diberi Ransum Mengandung Tepung Bulu Ayam - I Komang Budiarta; Ni Ketut Sri Rukmini; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2020)
The commodity of poultry that has the greatest potential to be developed is broiler chicken, this is because the growth rate is very fast so that the maintenance period is relatively short. Livestock productivity is influenced by 30% genetic factors and 70% environmental factors. One important environmental factor to consider is maintenance management, especially feed. Chicken feather flour is one of the wastes that can be used as chicken feed. The research design used was a Completely Randomized Design (CRD) with 4 treatments and 3 replications each test using 4 chickens. The four treatments are P0 = control ration without adding chicken feather flour, P1 = ration containing 2% chicken feather flour, P2 = ration containing 4% chicken feather flour, P3 = ration containing 6% chicken feather flour. The parameters observed were the weight of the carcass parts (chest, thighs, wings and back). The data obtained were analyzed by analysis of variance, if obtained significantly different data (P <0.05) will be followed by a multiple distance test from Duncan. Addition of chicken feather flour to broiler chicken ration gave no significant difference (P> 0.05) in the weight of carcass parts (chest, thighs, wings and back).